Thrombus formation on bioprosthetic aortic valves. (25th November 2020) - Bing, R; Andrews, J; Williams, M; Clark, T; Semple, S; Van Beek, E; Lucatelli, C; Sellers, S; Leipsic, J; Tavares, A; Stephens, A; Koglin, N; et al.
Abstract: Background: 18F-GP1 is a novel radiotracer with a high affinity for the platelet glycoprotein IIb/IIIa receptor. Subclinical bioprosthetic valve thrombus has been postulated as a trigger for accelerated valve degeneration. Purpose: To determine the feasibility of 18F-GP1 positron-emission tomography-computed tomography (PET-CT) for the detection of subclinical bioprosthetic aortic valve thrombus. Methods: (i) Explanted degenerated aortic valve prostheses underwent histology and imaging. (ii) In a prospective observational study, patients with bioprosthetic aortic valve replacement (AVR) underwent echocardiography and 18F-GP1 PET-CT. Valves were assessed for hypoattenuating leaflet thickening (HALT), hypo-attenuation affection leaflet motion (HAM) and GP1 uptake. Results: (i) GP1 correlated with thrombus on explanted valves (Figure). (ii) The first 6 patients (Table) were asymptomatic and had normally functioning surgical bioprostheses on echocardiography. At a median of 166 (range 122–189) days post-AVR, no patients had HALT or HAM on CT. There was avid focal GP1 uptake on the leaflets of all 6 patients which appeared most prominent along the leaflet edges (Figure). Only one patient had focal uptake in the valve frame, remote from the leaflets. In a separate cohort undergoing 18F-GP1 PET-CT for other conditions, there was no uptake on normal, native aortic valves (n=8). Conclusion: For the first time, we demonstrate that 18F-GP1 PET-CT is a highly sensitive method of assessing platelet activation on bioprosthetic aortic valves. Despite the absence of CT evidence, early thrombus appeared to be a universal finding on recently implanted valve prostheses. The biological and clinical implications of subclinical bioprosthetic aortic valve thrombus have yet to be established. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation